Penerapan Metode Bermain Untuk Meningkatkan Hasil Belajar Senam Lantai Pada Peserta Didik Kelas V Di SD NEGRI 1 POH BERGONG Tahun 2024/2025 - Kusuma, I Wayan Krisna Ananda Kusuma; Satyawan, I Made; Dartini, Ni Putu Dwi Sucita Dartini (Athena: Physical Education and Sports Journal, 2025)
Improving learning outcomes in floor exercise among elementary school students requires the implementation of appropriate and engaging learning strategies. The play method is considered an effective approach since it encourages motivation, confidence, and active participation of students in the learning process. This classroom action research was conducted in two cycles involving 24 fifth-grade students of SD Negeri 1 Poh Bergong in the 2024/2025 academic year. Each cycle consisted of planning, action, observation, and reflection stages, with instruments including floor exercise skill tests, student activity observation sheets, and teacher performance observation sheets. Data analysis revealed that in the first cycle, the students’ average learning outcome was only 72.1 with a mastery level of 4%, indicating that most students still had difficulties in performing the movements. After reflection and improvements through the application of the play method, the second cycle showed a significant improvement with an average score of 92.9 and mastery level reaching 96%. These findings demonstrate that the play method is effective in enhancing students’ floor exercise skills, particularly in forward and backward rolls. Moreover, the method contributes to building students’ confidence, discipline, and cooperation. Therefore, the play method can be recommended as an alternative learning strategy in Physical Education to improve learning outcomes in elementary schools.